Influence of seasonal dynamics on water quality, microbiome, and plant nutritional markers of an aquaponics system - Ibrahim, Labaran (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Restricted access. Expected release date 2025.
Keywords: Uncatalogued